Green synthesis of a lactoferrin-infused silver nanoparticle gel for enhanced wound healing - Ahmed K. Geneidy; Maii A. Abdelnaby; Doaa A. Habib; Heba M. Elbedaiwy; Kamel R. Shoueir (Scientific Reports)
Abstract The study analyzed the benefits of nano-silver (AgNPs) in reducing side effects and enhancing efficacy, highlighting the advantages compared to silver ions. The study examined the production of AgNPs-lactoferrin complexes (AgNPs-LTF) using bovine lactoferrin (LTF) at 1, 2, and 4 mM concentrations. The objective was to create an AgNPs-LTF gel with Carbopol as the base and assess its effectiveness in enhancing wound healing in rats. UV–Vis, PL, FTIR, and XRD analyses confirmed the synthesis of AgNPs. Microscopic examinations (TEM and SEM) showed mainly spherical AgNPs in the AgNPs-LTF samples, with diameters between 11 and 27 nm. The AgNPs-LTF gel with biologically processed AgNPs demonstrated effective infection control and enhanced wound healing outcomes. In Sprague–Dawley rats, the 4 mM AgNPs-LTF gel demonstrated significant wound closure, achieving complete closure by day 10, exceeding the healing rates of both the LTF and control groups. The AgNPs-LTF complex demonstrated high robustness and exceeded the performance of native LTF, exhibiting similar toxicity levels to AgNPs. The study shows the effectiveness of AgNPs-LTF gel in wound treatment, indicating its potential as a viable treatment option.